Implementasi Metode Regresi Linier Berganda Dalam Estimasi Tingkat Pendaftaran Mahasiswa Baru - Abdul Zikri Siregar (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
Every agency or an organization that wants to survive is needed to improve a proper service. Increasing the amount of capacity is an important thing to note, one way that can be done to estimate the amount of capacity is by data mining. The data mining method used in this case is to use the Multiple Linear Regression algorithm. This algorithm is an analysis that has more than one independent variable. This research was conducted at AMIK Tunas Bangsa Pematangsiantar, by analyzing the data for new students to estimate the number of new student admissions. From the results of this study, the estimated number of new students got 93 people, which previously was 107 people, which means that in the following year there was a decrease in the number of new students from the year previous. This study aims as a recommendation in improving future evaluation.